2014
DOI: 10.1007/s10545-014-9687-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and outcome in a series of 88 patients with the cblC defect

Abstract: No major differences were found between neonatal and early onset patients so that these groups were combined as an infantile-onset group representing 88 % of all cases. Hypotonia, lethargy, feeding problems and developmental delay were predominant in this group, while late-onset patients frequently presented with psychiatric/behaviour problems and myelopathy. Plasma total homocysteine was higher and methionine lower in infantile-onset patients. Plasma methionine levels correlated with "overall impression" as j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
165
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(184 citation statements)
references
References 57 publications
8
165
2
9
Order By: Relevance
“…Fischer et al [22] showed that treatment with parenteral hydroxocobalamin, betaine, folate/folinic acid, and carnitine improved biochemical abnormalities, but long-term neurological and ophthalmological outcomes were not affected significantly. On the contrary, in patient 1, neurological signs improved after proposed treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al [22] showed that treatment with parenteral hydroxocobalamin, betaine, folate/folinic acid, and carnitine improved biochemical abnormalities, but long-term neurological and ophthalmological outcomes were not affected significantly. On the contrary, in patient 1, neurological signs improved after proposed treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary methionine provides a source of methionine that may compensate in part for the defective intracellular synthesis of methionine that follows closely from the primary defect in cblC. Although patients with cblC were traditionally restricted in protein intake, in a recent survey, none of 88 European patients received protein restriction (Fischer et al 2014). Furthermore, recent studies of treatment in cblC found no benefit in restricting protein access and a possibly deleterious effect of using low-methionine medical foods (Manoli et al 2015).…”
Section: Pathophysiology Molecular Analyses and Treatment In Relatimentioning
confidence: 99%
“…Characteristic clinical manifestations of the early-onset type include feeding difficulties, failure to thrive, developmental delay, and muscular hypotonia (e.g., Fischer et al 2014;Rosenblatt et al 1997). Some earlyonset patients develop a hemolytic-uremic-like syndrome, optic atrophy, and congenital or acquired cardiomyopathy (Martinelli et al 2011), sometimes with noncompaction (Profitlich et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early-onset patients present with intrauterine growth retardation (IUGR), microcephaly, failure to thrive, developmental delay, hypotonia, progressive retinopathy, and maculopathy (Fischer et al 2014). Early-onset patients usually present in the first months of life and have an unfavorable prognosis (CarrilloCarrasco et al 2011).…”
Section: Introductionmentioning
confidence: 99%